KECENDERUNGAN PERKEMBANGAN KOTA AMBON: DAMPAKNYA TERHADAP KUALITAS LINGKUNGAN PESISIR TELUK AMBON DAN KERENTANANNYA TERHADAP BAHAYA TERKAIT DENGAN KENAIKAN MUKA LAUT - Wahyu Budi Setyawan; Wempi Barends; Ahmad Ainarwowan; Dominggus Polnaya (Pattimura University, 2022)
Ambon City, the capital of Maluku Province, is a coastal city where most of the land is the Ambon Bay coastal area. Along with the increase in population, Ambon City also continues to grow. Global sea-level rise is now likely to receive attention because of the impact it may have on coastal areas. By 2100, it is projected that sea levels will rise to 1.1 meters from the current sea level. As a coastal city, the trend of sea-level rise should be taken into account in the development of Ambon City. Visual analysis of the Ambon Bay satellite imagery from Google Earth and video recordings published on social media and the results of field observations of the Ambon Bay coastal area show that: (1) the coastal lowlands in the Ambon Bay coastal area have developed into densely populated built areas; (2) Ambon City is growing towards hilly areas; (3) along the coast of Ambon Bay, there are efforts to carry out reclamation and build coastal defense structures which are carried out personally by the coastal land authorities. This tendency has implications for (1) the decline in the environmental quality of the coastal area of Ambon Bay in several locations; and (2) increasing the level of vulnerability of coastal areas to hazards that may arise due to sea-level rise along the coast of Ambon Bay if the sea level rise scenario above actually occurs